Sintomas de ansiedade, depressão e estresse entre estudantes universitários durante a transição para atividades acadêmicas presenciais na pandemia da covid-19 - Berardi, Marilia Cristina (2024)
Introduction: Identifying the emotional and psychological changes of students upon partial return to face-to-face activities at the university makes it possible to determine the profile associated with the risk of mental health problems and outline support strategies for coping. Objective: To determine the prevalence of anxiety, depression and stress symptoms and their protective factors among Brazilian university students at a federal public university during the period of return to face-to-face activities after the pandemic. Material and methods: Descriptive, analytical, cross-sectional, observational study, with data collection carried out between January and March 2022, through self-application of the (DASS-21). Results: Among women who presented higher occurrences of mental symptoms, having an academic scholarship (OR= 2.41; 95% CI: 1.04-5.55), having a religious practice (OR= 3.37; 95% CI: 1.26-9.03) and being in a stable union (OR= 4.28; 95% CI: 1.76-10.42) are protective factors for mental symptoms. In men, the protective factors for mental symptoms are: studying in the exact area (OR= 7.75; CI 95%: 1.66-36.12), being in the first year of the course (OR= 0.23; CI95 %: 0.06- 0.89) and have an academic scholarship (OR= 0.17; CI 955: 0.04-0.70). Conclusion: The stability of the marital union, being a woman, having a support network and scholarship, religious practice and the area of activity can positively influence the mental health of this population group.